Regulation of STEAP1 gene and its clinical significance in human prostate cancer - Gomes, Inês Margarida Amaral Santos (2014)
The prostate gland is an accessory gland of the male reproductive system and displays a critical role in male fertility. This gland is dependent of sex steroid hormones, namely androgens and estrogens, for the gland morphogenesis, development and cellular homeostasis. Prostate cancer (PCa) is a multifactorial disease, affected by both endogenous and exogenous risk factors, especially family history, age and sex hormones. PCa is the second most common type of cancer among men, and along with BPH, is found in the majority of men over 40 years old. Although PCa etiology is complex, inflammatory processes are thought to be behind the appearance of pre-cancerous lesions. At molecular level, PCa is often described as a two step disease. Initially it is responsive to androgens, but usually, the PCa becomes androgen-independent. In the end, the clinical outcome of PCa is defined by the potential of the tumor to grow, invade and metastasize. Regardless of all the knowledge gathered from prostate cancer pathophysiology and clinical management, identification of genes associated with the pathology, the role of sex steroid hormones in their regulation, and their potential to be used as biomarkers or immunotherapeutic targets is urgent. STEAP1 was firstly identified as being overexpressed in prostate cancer. However, it can also be found overexpressed in several other types of tumors. STEAP1 expression in normal tissues is almost restricted to the prostate, where it is primarily localized in the plasma membrane of epithelial cells, especially at cell-cell junctions. STEAP1 regulation and biological function are yet uncertain, but it is believed to act as an ion channel or transporter protein, regulating inter- and intra-cellular communications. Finally, although its clinical significance is not clear, STEAP1 features stress its potential as biomarker and immunotherapeutic target. This way, it was evaluated if STEAP1 expression is regulated by sex steroid hormones, using both in vitro and in vivo assays. It was found that STEAP1 is down-regulated by DHT and E2 in LNCaP prostate cancer cells and in rat prostate, suggesting that STEAP1 may have a role on prostate cancer progression from androgen-dependent to androgen-independent. Subsequently, it was also evaluated the expression pattern of a STEAP1 related gene (STEAP1B) in cancer cell lines, and whether STEAP1 expression is subjected to posttranscriptional or post-translational regulatory mechanisms. In silico analysis revealed that STEAP1 and STEAP1B1 share high homology, and STEAP1 is more stable in prostate cancer cells rather than in non-malignant ones. Furthermore, it was demonstrated by in silico analysis that STEAP1 expression may be regulated by several post-translational modifications. In order to clarify the role of STEAP1 in prostate cancer, it was used a specific siRNA to decrease the levels of STEAP1 in LNCaP cells. Then, it was evaluated the role of STEAP1 in cell proliferation and apoptosis, as well as the effect of dihydrotestosterone (DHT) in LNCaP cells with low levels of STEAP1. Using MTS assay, flow cytometry and TUNEL assay, it was evident that STEAP1 gene silencing appears to reduce cell viability and growth, and to increase apoptosis of LNCaP cells. On the other hand, the DHT action seems to be dependent of STEAP1 levels as it could not revert the effects induced by STEAP1 knockdown. Much effort has been done to clarify the potential of STEAP1 as biomarker and immunotherapeutic target. Here, it was investigated the association between STEAP1 expression with histologic and clinical data of patients. It was demonstrated that STEAP1 is overexpressed in PCa and PIN lesions, and it is positively associated with Gleason score. Taken together, the results here presented demonstrate that STEAP1 expression is negatively regulated by the two main sex steroid hormones presents on prostate. STEAP1 high stability in prostate tumor cells in comparison to normal ones lead us to believe that post-transcription and translational regulation mechanisms are dependent on the tumor stage. Moreover, STEAP1 gene silencing inhibits cell viability and proliferation, ate the same time that increases apoptosis in LNCaP cells, suggesting that STEAP1 may have an important role on PCa progression from androgen-dependent to hormone refractory. The use of STEAP1 per se may not be sufficient to be used as a biomarker in the daily clinical practice, but may open novel strategies for diagnosis and treatment of prostate cancer.